Efektivitas Ekstrak Etanol Buah Pare (Momordica Charantia) dalam Penyembuhan Luka Sayat pada Mencit - Isma Nur Astriyani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Wounds are a condition where the integrity of the skin is disrupted, often requiring a fast and accurate healing process to prevent infection. Bitter melon (Momordica charantia L) is known to have chemical components that potentially accelerate the wound healing process. This study aims to test the effectiveness of bitter melon extract in accelerating wound healing in mice (Mus musculus). The research method used is an experimental method with a post-test only control group design. This study involved 30 mice divided into five treatment groups: negative control, positive control, and three treatment groups with different concentrations of bitter melon extract. The results showed that bitter melon extract could accelerate wound healing in mice, indicated by a significant decrease in wound length in the treatment groups compared to the control groups. Therefore, bitter melon extract has the potential to be used as an alternative treatment to accelerate the wound healing process.